ANALISIS PENENTUAN KONFIGURASI JARINGAN DISTRIBUSI TERBAIK ANTARA WAREHOUSE DAN DEMAND REGION DENGAN MENGGUNAKAN MODEL BI-CRITERIA - Yusuf, Muhammad; Sodikin, Imam (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Determining the best level of aggregation in a centralized supply chain is one of the most difficult problems because of the conflicting objectives and demand uncertainty. PT. Nampar Nos is one of leading drinking water company with various range market in some regions in Flores, even in some islands in East of Nusa Tenggara. It’s width service area and demand uncertainty. Causes the company has a good decision to decide where the warehouse should be located, and how much the optimal number of warehouses to satisfy the demand. This research uses bi-criteria model to determine the best distribution network between Warehouse and Demand Region. There are two steps in data process-ing that will be done. The first step is to determine the cost that relation with the old distri-bution network in Flores use Gaur and Ravindran model and the second step is to de-velop the new alternative use trial and error method and then calculate the total cost and also responsiveness. After the solver output, we get the best one configuration from 2 alternative configuration distribution network that is developed. Alternative 1 is the best configuration network amount warehouse and demand region which is yield in decreasing total cost per month about Rp 49.996.000 or 11% from level Rp 417.280.400 to Rp 367.284.400. And also decreasing product miles about 7.500 or 5% from 153.500 become 146.000.